2016
DOI: 10.1186/s12933-016-0362-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin receptor substrate-1 polymorphisms and high platelet reactivity with clopidogrel therapy in coronary artery disease patients with type 2 diabetes mellitus

Abstract: BackgroundThe mechanisms leading to the high on-treatment platelet reactivity in diabetes patients are not fully elucidated. The genetic factors may be associated with the diminished antiplatelet efficacy of dual antiplatelet therapy. We investigated the possible association between insulin receptor substrate-1 (IRS-1) polymorphisms and high platelet reactivity in coronary artery disease (CAD) patients with type 2 diabetes mellitus (T2DM).MethodsA total of 674 CAD patients with T2DM were enrolled in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…CAD develops as a result of vascular tract stenosis or occlusion caused by coronary atherosclerotic lesions and several environmental and lifestyle factors (Campbell et al, 1998;Erbel and Görge, 2014;Bullock-Palmer, 2015). Previous experimental studies at the molecular level have indicated that many genetic factors, including the genes encoding angiotensinogen and angiotensin-converting enzyme, hepatic lipase, insulin receptor substrate-1, kinesin family member 6, cholesteryl ester transfer protein, ATP-binding cassette subfamily A member 1, and apoptotic extrinsic death receptor, have an important role in the risk of CAD development (Bonfim-Silva et al, 2016;Cyrus et al, 2016;Kishore Kumar et al, 2016;Mohammadzadeh et al, 2016;Vatte et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CAD develops as a result of vascular tract stenosis or occlusion caused by coronary atherosclerotic lesions and several environmental and lifestyle factors (Campbell et al, 1998;Erbel and Görge, 2014;Bullock-Palmer, 2015). Previous experimental studies at the molecular level have indicated that many genetic factors, including the genes encoding angiotensinogen and angiotensin-converting enzyme, hepatic lipase, insulin receptor substrate-1, kinesin family member 6, cholesteryl ester transfer protein, ATP-binding cassette subfamily A member 1, and apoptotic extrinsic death receptor, have an important role in the risk of CAD development (Bonfim-Silva et al, 2016;Cyrus et al, 2016;Kishore Kumar et al, 2016;Mohammadzadeh et al, 2016;Vatte et al, 2016;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms leading to the high on-treatment platelet reactivity in T2DM patients are not fully elucidated and could potentially involved genetic factors [26]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of the IRS-1 genotype on prediabetic mediated features were not known. Recently the researchers showed that this gene is not only associated with Type 2 diabetes in different populations but also it may have a significant correlation with diabetic complications, particularly with coronary artery disease (CAD) and obesity (9)(10)(11). Another gene that was investigated in this study was perilipin (PLIN) (rs4578621).…”
Section: Introductionmentioning
confidence: 87%